Redistribution and Insurance in Welfare States around the World - Charlotte Bartels; Dirk Neumann (The Scandinavian Journal of Economics, 2021)
Redistribution across individuals within the framework of a one-year period is an empirically intensely studied question. However, a substantial share of annual redistribution might turn out to serve individual insurance in a longer perspective, reducing the level of actual redistribution across individuals. In this paper, we investigate to what extent long-run redistribution diverges from annual redistribution in welfare states of different types. Exploiting panel data from the Cross-National Equivalent File (CNEF) for Australia, Germany, South Korea, Switzerland, the United Kingdom, and the United States, we find that welfare states such as Germany that are assumed to engage in a high level of redistribution actually achieve relatively less redistribution between individuals in the long run than the United Kingdom or the United States. Regression results show that a higher share of elderly in a country is associated with more annual redistribution, but with less long-run redistribution between individuals. The results suggest that, in welfare states with aging populations, we might expect growing annual redistribution that, to a substantial extent, is in fact income smoothing for the elderly.
Additional information: Open access funding enabled and organized by Projekt DEAL
Keywords: D31; D63; H53; H55; I38; 330; Insurance; Redistribution; Welfare states